Impact of clinical pharmacist intervention in chronic obstructive pulmonary disease management - Moses, Jackin R.; E. M., Neena Priyamalar; Ravi, Shilpa; Balakrishnan, Raveena Pachal; Ravichandran, Rajganesh; Selvaraj, Lavanya (International Journal of Research in Medical Sciences, 2020)
Background: Chronic obstructive pulmonary disease (COPD) is a common, preventable, and treatable disease characterized by persistent respiratory symptoms and airflow limitation. In 2016, COPD is the third leading cause of death globally and is projected to increase by more than 30% in the next 10 years. The main threat to the prognosis lies in the lack of disease knowledge, poor medication adherence, and health-related quality of life. Clinical Pharmacist is a key profession to improve patient care in COPD management and literature in this regard is very limited. It is important to establish the impact of a clinical pharmacist as an indicator to improve patient outcomes. Hence the aim of this was to assess the Impact of Clinical Pharmacist Intervention in COPD management in a Tertiary care hospital. Methods: The study was conducted as a prospective and interventional. A total of 53 patients were recruited in the study. The study participants were educated by a clinical pharmacist on disease state, medications, and breathing techniques. Patients have a regular follow-up after 6 months during a scheduled visit. Questionnaires were administered to all patients at baseline and 6 months to assess their medication adherence, disease-related knowledge, and HRQoL. Results: Out of 53 study participants, the majority of COPD patients 23 (46.94%) were found to be in the elderly age group of 60-69 years. The majority of the patients were in a severe category of 48.98%. Thereafter intervention assessment of COPD related knowledge showed a 33.45% improvement. The majority of study participants showed high adherence after the intervention of 46.94 %. All aspects of the HRQoL questionnaire showed improvement after intervention. The results were statistically significant. Conclusions: The Pharmacist-led COPD Intervention showed improvement in the three main aspects of the study. It confirms the need for healthcare systems to recognize the role of clinical pharmacists in both pharmacological therapy and non-pharmacological supportive care.